The robot eyes don't have it. The presence of eyes on collaborative robots yields marginally higher user trust but lower performance - Artur Pilacinski; Ana Pinto; Soraia Oliveira; Eduardo Araújo; Carla Carvalho; Paula Alexandra Silva; Ricardo Matias; Paulo Menezes; Sonia Sousa (Heliyon, 2023)
Eye gaze is a prominent feature of human social lives, but little is known on whether fitting eyes on machines makes humans trust them more. In this study we compared subjective and objective markers of human trust when collaborating with eyed and non-eyed robots of the same type. We used virtual reality scenes in which we manipulated distance and the presence of eyes on a robot's display during simple collaboration scenes. We found that while collaboration with eyed cobots resulted in slightly higher subjective trust ratings, the objective markers such as pupil size and task completion time indicated it was in fact less comfortable to collaborate with eyed robots. These findings are in line with recent suggestions that anthropomorphism may be actually a detrimental feature of collaborative robots. These findings also show the complex relationship between human objective and subjective markers of trust when collaborating with artificial agents.